Factors that contribute to juvenile delinquency: A case study on male juveniles in Henry Gurney Melaka / Siti Nur Edlyn Nadia Zuraiju and Vidya Yazmin Muhammad Yahya - Zuraiju, Siti Nur Edlyn Nadia; Muhammad Yahya, Vidya Yazmin (Faculty of Administrative Science and Policy Studies, 2012)
Social deviance among juveniles starts at school age. At the initial stage this delinquency is in the form of abuse of school rules such as truancy, smoking and vandalism. The absence of effective measures to curband overcome this problem is a catalyst to more serious criminal misconduct such as bullying, injury to others, rape, theft and murder. Effective preventive and rehabilitative measures must be implemented in an integrated and widespread manner at the family and community levels, school and rehabilitation institutions in view of the fact that the younger generation will inherit the nation‟s wealth, place, and profession. The increase in criminal misconduct among adolescents is influenced by several factors particularly involving those directly involved with adolescent development such as parents, the school, the family, social institutions, the community and more. Juveniles can be concluded as a group of adolescents under the age of 21 years and who have criminal responsibility at the age of 10 years. This paper focuses on adolescents aged between 14 and 21 years. In this research, we will study on factors that contribute to juvenile delinquency based on three factors which are family, peer pressure and environmental factors.